CREATING SENSATION OF LEARNING IN CLASSROOM: USING 'GATHER TOWN' PLATFORM VIDEO GAME-STYLE FOR VIRTUAL CLASSROOM - Nur Fitria, Tira (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: Virtual classes have now become commonplace during the COVID-19 pandemic. As time goes by, applications for virtual meetings continue to appear, one of which is Gather Town, which is now widely used and is a tight competitor to Zoom Meeting and Google Meet. Gather Town is a virtual meeting platform designed like a video game. This research is to implement the use of the 'Gather Town' game platform and to find out the student’s perception during the implementation and simulation of Gather Town application as an alternative platform in creating a sensation of English Language Learning (ELL) in the real classroom through virtual class during the pandemic COVID-19. This study uses descriptive qualitative research. The result analysis from observation and interview show that Gather Town has graphics similar to the Harvest Moon game, where students can play one character and can write their name on the top so that the lecturer can see which students are present. The room is designed similar to a classroom, where the lecturer's desk is at the front of the classroom. The virtual classroom also has chairs that are neatly lined up like classrooms in the real world. Then when doing group assignments, the student characters will gather at the same table as in a real classroom. They also carry out group work activities as if they were in the classroom. Each group sat in a circle and discussed with one another. The current game may be an alternative design in a virtual classroom. Abstrak: Kelas virtual kini menjadi hal biasa selama pandemi COVID-19. Seiring berjalannya waktu, aplikasi untuk virtual meeting terus bermunculan, salah satunya adalah Gather Town yang kini banyak digunakan dan menjadi pesaing ketat Zoom Meeting dan Google Meet. Gather Town adalah platform pertemuan virtual yang dirancang seperti gim video. Penelitian ini bertujuan untuk mensimulasikan penggunaan platform game 'Gather Town' dan mengetahui persepsi siswa selama simulasi aplikasi Gather Town sebagai platform alternatif dalam menciptakan sensasi Pembelajaran Bahasa Inggris di kelas nyata melalui virtual. kelas selama pandemi COVID-19. Penelitian ini merupakan penelitian kualitatif deskriptif. Hasil analisis dari observasi dan wawancara menunjukkan bahwa Gather Town memiliki grafik yang mirip dengan game Harvest Moon, dimana mahasiswa dapat memainkan satu karakter dan dapat menuliskan namanya di bagian atas sehingga dosen dapat melihat mahasiswa mana yang hadir. Tidak hanya itu, ruangannya didesain mirip dengan ruang kelas, dimana meja dosen berada di bagian depan kelas. Ruang kelas virtual juga memiliki kursi yang berjejer rapi seperti ruang kelas di dunia nyata. Kemudian saat mengerjakan tugas kelompok, karakter siswa akan berkumpul di meja yang sama seperti di ruang kelas yang sebenarnya. Mereka juga melakukan kegiatan kerja kelompok seolah-olah berada di dalam kelas. Setiap kelompok duduk melingkar dan berdiskusi satu sama lain. Game saat ini dapat menjadi alternatif desain di kelas virtual.